Research trends of acupuncture therapy for painful peripheral nervous system diseases from 2004 to 2023: a bibliometric and meta-analysis - Fan, Binke; Xia, Yunfan; Feng, Yuanyuan; Yang, Xilong; Lin, Ping; Fang, Jianqiao; Zhang, Zuyong; Li, Shimin (Frontiers in Neurology, 2025)
BackgroundPeripheral nervous system diseases (PNSD) have represented a major global health burden, leading to significant economic impacts and diminished productivity. This bibliometric analysis was performed to summarize the current research trends and hotspots over the past two decades, aiming to provide a comprehensive perspective for future research.MethodsAll data were sourced from the Web of Science Core Collection (WoSCC) on March 1, 2024, for publications between January 1, 2004, and December 31, 2023. Data visualization and analyses, including descriptive statistics, co-occurrence mapping, and cluster analysis, were performed using CiteSpace (Version 6.1.R6) and Excel 2021.ResultsOur search yielded 678 references, with the annual publication count demonstrating an increasing trend over the past 20 years. The most productive country and institution were China and Kyung Hee University, respectively. Fang Jianqiao, was the most prolific author with the highest publications. Among journals, “Pain,” was the most frequently cited, while the top-cited reference was a randomized controlled pilot trial by Lu Weidong in 2020. “Acupuncture” emerged as the keyword with the highest frequency. The meta-analysis indicated that acupuncture was more effective than standard care for pain associated with Diabetic Peripheral Neuropathy [MD = −2.03, 95% CI (−2.86, −1.21), 2 RCTs, 102 participants, p < 0.0001].ConclusionOur bibliometric review revealed key insights into the focal areas of PNSD research, underscoring the urgent need for continued and targeted high-quality investigations.